Pentiptycene-based microporous polymer for removal of organic dyes from water. (November 2019) - Ou, Qiang; Zhang, Qing-Mei; Zhu, Peng-Cheng; Zhang, Qing-Pu; Cheng, Zhiming; Zhang, Chun
Graphical abstract: Highlights: Novel H-shaped pentiptycene is used as monomer for microporous polymer. Cost-effective synthetic strategy is used for adsorbent materials to remove organic dyes from water. The obtained polymer PHCP exhibits high BET surface area and superior adsorption capacities for organic dyes. Abstract: A pentiptycene-based hyper-cross-linked polymer (PHCP) was synthesized by low-effective Friedel-Crafts reaction using rigid H-shaped pentiptycenes as monomers. The obtained PHCP exhibits a high BET surface area of 1074 m 2 g −1, outstanding CO2 and H2 storage capacities. Moreover, PHCP displayed superior adsorption capacities for organic dyes with the maximum adsorption capacities for Crystal Violet (CV) and Methylene Blue (MEB) were 877 and 289 mg g −1, respectively. With high surface area and hierarchical porous structure, PHCP may be a potential adsorbent for the removal of organic dyes from water.